(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
The clavicle bone is an essential anatomical structure that plays a crucial role in shoulder girdle function, as it serves as an attachment site for various muscles and ligaments. The clavicle bone is also important in forensic medicine, as it is frequently used for age and sex estimation. The aim of this study is to perform a morphometric analysis of fully ossified clavicle bones in the North Indian population and compare our findings with previous studies. The clavicle is considered to be an important bone when dealing with sex differences in skeletal material. The present study included 84 fully ossified clavicle bones (42 right-sided and 42 left-sided) of unknown sex and age. Parameters like maximum length, acromial breadth and height, and sternal breadth and height of clavicles were studied. All measurements were taken with the help of a vernier caliper and measured in mm. The maximum length, height, and width of the sternal end of the clavicle were found to be higher in the left-sided clavicle, while the height and width of the acromial end of the clavicles were found to be higher in the right-sided clavicles. These variations could be due to racial, genetic, or mechanical factors. These findings may be helpful to orthopedic surgeons involved in the surgical correction procedures of clavicle fractures.